Recent African origin of modern humans revealed by complete sequences of hominoid mitochondrial DNAs. - Horai, S (1995)
We analyzed the complete mitochondrial DNA (mtDNA) sequences of three humans (African, European, and Japanese), three African apes (common and pygmy chimpanzees, and gorilla), and one orangutan in an attempt to estimate most accurately the substitution rates and divergence times of hominoid mtDNAs. Nonsynonymous substitutions and substitutions in RNA genes have accumulated with an approximately clock-like regularity. From these substitutions and under the assumption that the orangutan and African apes diverged 13 million years ago, we obtained a divergence time for humans and chimpanzees of 4.9 million years. This divergence time permitted calibration of the synonymous substitution rate (3.89 x 10(-8)/site per year). To obtain the substitution rate in the displacement (D)-loop region, we compared the three human mtDNAs and measured the relative abundance of substitutions in the D-loop region and at synonymous sites. The estimated substitution rate in the D-loop region was 7.00 x 10(-8)/site per year. Using both synonymous and D-loop substitutions, we inferred the age of the last common ancestor of the human mtDNAs as 143,000 +/- 18,000 years. The shallow ancestry of human mtDNAs, together with the observation that the African sequence is the most diverged among humans, strongly supports the recent African origin of modern humans, Homo sapiens sapiens.